Muscle-inspired MXene/PVA hydrogel with high toughness and photothermal therapy for promoting bacteria-infected wound healing. (17th January 2022) - Li, Yan; Han, Miaomiao; Cai, Yue; Jiang, Bing; Zhang, Yuanxin; Yuan, Biao; Zhou, Feng; Cao, Chongjiang
Abstract : MXene@PVA antibacterial hydrogel with excellent mechanical properties was prepared using a directional freezing-assisted salt dissolution method. Combined with photothermal treatment, it could effectively promote bacteria-infected wound healing. Abstract : The process of wound healing is often accompanied by bacterial infection, which is a serious threat to human health. The abuse of antibiotics in traditional therapy aggravates the resistance of bacteria and gradually reduces the therapeutic effect. Therefore, it is important to develop effective antibacterial dressings to promote wound healing and prevent infection. Photothermal therapy (PTT) is considered a quick and reliable method of suppressing bacterial infections without developing drug resistance. The unique network structure and high water retention of hydrogel help wound healing. Inspired by the hierarchical assembly of anisotropic structures across multiple length scales of muscles, herein a directional freezing-assisted salting-out method was used to prepare anisotropic MXene@PVA hydrogels. The hydrogel not only had excellent mechanical properties (stress up to 0.5 MPa and strain up to 800%), but could also be used for local hyperthermia of infected sites using an NIR laser (808 nm). Owing to the excellent photothermal properties of MXene, its main antibacterial mechanism is hyperthermia and the hydrogel showed broad-spectrum antibacterial activity against Gram-positive and Gram-negative bacteria (inhibition rates of Escherichia coli and Staphylococcus aureus were 98.3 and 95.5% respectively). In addition, it could effectively promote the proliferation of NIH-3T3 cells. In mouse wound models, the hydrogel was effective in inhibiting wound infection and promoting skin wound healing (the rate of wound closure was 98%). These results indicated that the MXene@PVA hydrogel, with high toughness and anisotropy properties, has the potential to be an excellent antibacterial wound healing dressing.